Heat-conducting epoxy adhesive film and preparation method thereof

By using silicon powder combination and optimization processes of different particle sizes in the epoxy film, the problems of slow solvent volatility and poor bubble discharge effect during the preparation process of the existing epoxy film are solved, and high thermal conductivity, stability and production efficiency are improved.

CN119592280AActive Publication Date: 2025-03-11JIANGSU KEMAITE TECH DEV CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411841142.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the preparation process, the existing epoxy films have slow solvent volatility, poor hot pressing and bubble discharge effect, and high overflow rate of the glue layer, resulting in uneven film surfaces, affecting performance, and low production efficiency.

Method used

The combination of silicon micro powders (2um, 0.5um, 4um) of different particle sizes is used as fillers, and the thermally conductive epoxy adhesive film is prepared through mixing, stirring, defoaming, coating, solvent removal and composite steps, and the process window is optimized to improve the thermal conductivity and dimensional stability of the adhesive film.

Benefits of technology

The thermal conductivity of the epoxy adhesive film is improved, the thermal expansion coefficient is reduced, the dimensional stability and adhesive performance are improved, the overflow rate of the adhesive layer is reduced, the flatness and thermal conductivity of the film surface are improved, and the production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592280A_ABST
    Figure CN119592280A_ABST
Patent Text Reader

Abstract

The invention relates to a heat-conducting epoxy adhesive film and a preparation method thereof. The heat-conducting epoxy adhesive film comprises the following components: 10-12 parts of epoxy resin, 5-12 parts of a curing agent, 0.015-0.11 part of an accelerant, 28-80 parts of inorganic filler, 0.1-0.5 part of pigment, 0.4-1 part of a coupling agent and 0.3-1.2 parts of a toughening agent, the inorganic filler is silica powder, the silica powder comprises silica powder with the particle size of 2 microns, silica powder with the particle size of 0.5 microns and silica powder with the particle size of 4 microns, and the preparation method comprises the following steps: S1, mixing materials; step S2, coating is carried out; step S3, surface drying; the preparation method has the advantages that the epoxy resin, the phenolic aldehyde curing agent, the imidazole accelerant, the silica powder, the pigment, the coupling agent and the flexibilizer are combined, and the epoxy adhesive film is prepared through the steps of mixing, stirring, defoaming, coating, solvent removing and compounding, so that the production efficiency of the epoxy adhesive film is improved, the highest baking temperature of a coating oven is reduced, and the technical indexes of the epoxy adhesive film are widened; the room-temperature storage stability is prolonged, the heat conductivity is improved, the dimensional stability in the use process is improved, the binding force of the copper material is improved, and the use performance of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of epoxy resin film preparation, and in particular to a thermally conductive epoxy film and a preparation method thereof. Background Art

[0002] In modern electronic packaging technology, epoxy film is widely used in the packaging of various electronic components due to its excellent bonding performance, electrical performance and chemical stability. However, with the development of electronic equipment towards miniaturization, high integration and high frequency, higher requirements are placed on the performance of epoxy film, such as good adhesion, low thermal expansion coefficient, high glass transition temperature, etc. During the use of the film, the film's bubble removal effect and the overflow rate of the glue layer are also important factors affecting its plastic packaging qualification rate.

[0003] However, in the preparation process of existing epoxy films, the evaporation rate of the solvent is slow and the high-boiling-point solvent has a good film-forming effect, but the oven temperature required for solvent removal is high and the coating production efficiency is low. During the hot pressing process of the epoxy film, the degassing effect is poor, and the overflow rate of the adhesive layer after bonding is large, resulting in insufficient dielectric thickness and uneven film surface, which affects the performance of the film after curing. As a result, it is necessary to increase the temperature from low temperature to high temperature for additional degassing, which affects the production efficiency of the application end.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention discloses a thermally conductive epoxy film and a preparation method thereof.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A thermally conductive epoxy film, comprising the following components by weight:

[0008] 10-12 parts of epoxy resin, 5-12 parts of curing agent, 0.015-0.11 parts of accelerator, 28-80 parts of inorganic filler, 0.1-0.5 parts of pigment, 0.4-1 parts of coupling agent, 0.3-1.2 parts of toughening agent; the inorganic filler is silicon micropowder, and the silicon micropowder includes silicon micropowder with a particle size of 2um, silicon micropowder with a particle size of 0.5um and silicon micropowder with a particle size of 4um.

[0009] Furthermore, the silicon micropowder with a particle size of 2 um accounts for 5 to 30% of the inorganic filler, the silicon micropowder with a particle size of 0.5 um accounts for 15 to 18.75% of the inorganic filler, and the silicon micropowder with a particle size of 4 um accounts for 60 to 75% of the inorganic filler.

[0010] Furthermore, the epoxy resin includes phenolic epoxy resin, biphenyl epoxy resin, naphthol epoxy resin, dicyclopentadiene epoxy resin and a combination thereof.

[0011] Furthermore, the curing agent includes a phenolic curing agent.

[0012] Furthermore, the accelerator includes an imidazole accelerator.

[0013] Furthermore, the toughening agent includes a core-shell toughening agent.

[0014] Furthermore, the coupling agent includes a silane coupling agent.

[0015] Furthermore, the pigment includes carbon black.

[0016] A method for preparing a thermally conductive epoxy film comprises the following steps:

[0017] Step S1, mixing: putting epoxy resin, curing agent, solvent and toughening agent into a stirrer and stirring to fully dissolve the resin and mix evenly to obtain a resin mixture; putting inorganic filler, pigment, coupling agent and toughening agent into a stirrer and stirring to obtain modified pigments and fillers; adding the modified pigments and fillers into the resin mixture, stirring, and then performing three-roll grinding and dispersion; then adding an accelerator, and performing vacuum degassing on the mixture to finally obtain a resin composition;

[0018] Step S2, coating the resin composition on the base film;

[0019] Step S3, surface drying, stepwise solvent removal of the base film, and three-stage heating to obtain an epoxy resin film;

[0020] Step S4, compounding the epoxy resin film and the protective film, and finally rolling them up.

[0021] Furthermore, in step S1, the stirring speed of the epoxy resin, curing agent, solvent and toughening agent is 300rpm-500rpm, and the stirring time is 30min; the stirring temperature of the inorganic filler, pigment, coupling agent and toughening agent is 120°C, the stirring time is 1h, and the stirring speed is 800rpm-1000rpm; the stirring speed of the modified color filler and resin mixture is 600rpm-800rpm, and the stirring time is 60min; the feed gap of the three-roll grinding dispersion is 50um, the discharge gap is 30um, the feed gap is 30um, and the discharge gap is 10um; the vacuum degassing speed is 400rpm-600rpm, and the time is 6min-8min.

[0022] Further, in step S3, the first step temperature range is 40-60°C, the second step temperature range is 80-95°C, and the third step temperature range is 70-80°C.

[0023] Furthermore, in step S4, the composite temperature range is 80-110°C.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1. The epoxy resin, phenolic curing agent, imidazole accelerator, silicon powder, pigment, coupling agent, toughening agent and other raw materials are prepared through the steps of mixing, stirring, degassing, coating, solvent removal, compounding and other steps. The filler combination of different particle sizes is introduced to improve the thermal conductivity of the epoxy film, reduce the thermal expansion coefficient, and improve its dimensional stability. The film has good stability, bonding performance and surface roughness. After the film is applied, the film surface is flat, the overflow rate of the adhesive layer is small, and the film surface is matte, which is conducive to copper deposition and copper coating.

[0026] 2. Use 2um silica powder as filler, and use it with 0.5um and 4um fillers to improve the surface roughness of the epoxy film after film formation, improve the coating and baking efficiency, and make the solvent volatilize faster during the preparation process of the film, meet the production needs of large-width films, and greatly improve production efficiency.

[0027] 3. Optimize the process window and expand the residual tolerance of the finished product. Ensure that the various components are fully dissolved in each other, the fillers are evenly stacked and filled at different depths of the resin, and reduce the impact of residual solvents in the film on the surface dryness.

[0028] 4. The film is baked at a relatively low temperature with a high boiling point solvent to reduce the degree of semi-curing reaction, which is beneficial to prolong the gel time of the film. It not only controls the film in a soft state, but also prolongs the storage stability of the film at room temperature.

[0029] 5. Hot pressing and laminating is carried out under the temperature window suitable for the adhesive film. The exhaust effect is good, the fluidity of the adhesive layer is small, and the overflow rate is small, which is beneficial to the flatness of the film surface; the film surface is matte, which is conducive to copper deposition and copper coating, improves the bonding strength with metal / non-metal, and improves the performance of the product.

[0030] 6. Use 2um silica powder as filler, and use it with 0.5um and 4um fillers to supplement the heat conduction channel and improve the thermal conductivity of the film after curing. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the appearance of the natural bonding of Example 1 after baking at 150° C. for 30 minutes.

[0032] Figure 2 This is a schematic diagram of the appearance of the natural bonding of Example 2 after baking at 150°C for 30 minutes.

[0033] Figure 3This is a schematic diagram of the appearance of the natural bonding of Example 3 after baking at 150° C. for 30 minutes.

[0034] Figure 4 This is a schematic diagram of the appearance of the natural bonding of comparative example 1 after baking at 150°C for 30 minutes.

[0035] Figure 5 This is a schematic diagram of the appearance of the natural bonding of comparative example 2 after baking at 150°C for 30 minutes.

[0036] Figure 6 This is a schematic diagram of the appearance of the natural bonding of comparative example 3 after baking at 150°C for 30 minutes.

[0037] Figure 7 Schematic diagram of the steps for thermal conductive epoxy film. DETAILED DESCRIPTION

[0038] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.

[0039] Embodiment 1:

[0040] A thermally conductive epoxy film comprises 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silicon micropowder (20 parts of particle size 2um, 12 parts of particle size 0.5um) and 4um), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent and 15 parts of butyl ester.

[0041] The coupling agent is a silane coupling agent, the toughening agent is a core-shell toughening agent, and the pigment is carbon black.

[0042] Its preparation method, such as Figure 7 As shown, the following steps are included:

[0043] Step S1, mixing: put phenolic epoxy resin, phenolic curing agent, solvent and toughening agent into a stirrer, set the speed to 500rpm, stir for 30 minutes, make the resin fully dissolved and mix evenly. Use a planetary mixer to mix the inorganic filler, pigment, coupling agent and toughening agent evenly, and stir for 1h at 120°C for modification; use mechanical stirring to add the modified color and filler mixture to the resin curing agent mixture, adjust the speed to 800rpm, stir for 60 minutes, and evenly disperse the silicon powder in the mixture. Set the feed gap to 50um, the discharge gap to 30um, the feed gap to 30um, and the discharge gap to 10um for three-roll grinding and dispersion; finally, add the accelerator and degas the mixture under vacuum conditions for 8 minutes to remove bubbles in the mixture.

[0044] Step S2: coating the resin composition on the base film, and controlling the thickness of the dry glue to be 130 um.

[0045] Step S3, surface drying, the base film is baked at a step-by-step temperature, and the solvent is removed by a three-stage heating method, first heating at 40°C, then heating at 80°C, and finally heating at 70°C. The heating time is controlled at 10.5 minutes, and the epoxy resin film is formed.

[0046] Step S4, compounding the epoxy resin film and the protective film at a temperature of 80° C. and a pressure of 2 MPa, and then rolling them up.

[0047] Embodiment 2:

[0048] A thermally conductive epoxy film comprises 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silicon micropowder (a particle size of 2 μm (10 parts) is used in combination with a particle size of 0.5 μm (14 parts) and 4 μm (56 parts)), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent and 15 parts of butyl ester.

[0049] The coupling agent is a silane coupling agent, the toughening agent is a core-shell toughening agent, and the pigment is carbon black.

[0050] The preparation method thereof comprises the following steps:

[0051] Step S1, mixing: put phenolic epoxy resin, phenolic curing agent, solvent and toughening agent into a stirrer, set the speed to 500rpm, stir for 30 minutes, make the resin fully dissolved and mix evenly. Use a planetary mixer to mix the inorganic filler, pigment, coupling agent and toughening agent evenly, and stir for 1h at 120°C for modification; use mechanical stirring to add the modified color and filler mixture to the resin curing agent mixture, adjust the speed to 800rpm, stir for 60 minutes, and evenly disperse the silicon powder in the mixture. Set the feed gap to 50um, the discharge gap to 30um, the feed gap to 30um, and the discharge gap to 10um for three-roll grinding and dispersion; finally, add the accelerator and degas the mixture under vacuum conditions for 8 minutes to remove bubbles in the mixture.

[0052] Step S2: coating the resin composition on the base film, and controlling the thickness of the dry glue to be 130 um.

[0053] Step S3, surface drying, the base film is heated in a stepwise manner, and the solvent is removed by a three-stage heating method, first heating at 50° C., then heating at 90° C., and finally heating at 70° C. The heating time is controlled at 14 minutes, and the epoxy resin film is obtained.

[0054] Step S4, compounding the epoxy resin film and the protective film at a temperature of 80° C. and a pressure of 2 MPa, and then rolling them up.

[0055] Embodiment 3:

[0056] A thermally conductive epoxy film comprises 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silicon micropowder (particle size 2um (5 parts) is used in combination with particle size 0.5um (15) and 4um (60 parts)), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent and 15 parts of butyl ester.

[0057] The coupling agent is a silane coupling agent, the toughening agent is a core-shell toughening agent, and the pigment is carbon black.

[0058] The preparation method thereof comprises the following steps:

[0059] Step S1, mixing: put phenolic epoxy resin, phenolic curing agent, solvent and toughening agent into a stirrer, set the speed to 500rpm, stir for 30 minutes, make the resin fully dissolved and mix evenly. Use a planetary mixer to mix the inorganic filler, pigment, coupling agent and toughening agent evenly, and stir for 1h at 120°C for modification; use mechanical stirring to add the modified color and filler mixture to the resin curing agent mixture, adjust the speed to 800rpm, stir for 60 minutes, and evenly disperse the silicon powder in the mixture. Set the feed gap to 50um, the discharge gap to 30um, the feed gap to 30um, and the discharge gap to 10um for three-roll grinding and dispersion; finally, add the accelerator and degas the mixture under vacuum conditions for 8 minutes to remove bubbles in the mixture.

[0060] Step S2: coating the resin composition on the base film, and controlling the thickness of the dry glue to be 130 um.

[0061] Step S3, surface drying, the base film is heated in a stepwise manner, and the solvent is removed by a three-stage heating method, first heating at 60°C, then heating at 95°C, and finally heating at 80°C. The heating time is controlled at 17.5 minutes, and the epoxy resin film is formed.

[0062] Step S4, compounding the epoxy resin film and the protective film at a temperature of 80° C. and a pressure of 2 MPa, and then rolling them up.

[0063] Embodiment 4:

[0064] The difference from Example 1 is that the epoxy resin used is a biphenyl type epoxy resin.

[0065] The performance of the product prepared is similar to that of the product prepared in Example 1.

[0066] Embodiment 5:

[0067] The difference from Example 1 is that the epoxy resin used is naphthol epoxy resin.

[0068] The performance of the product prepared is similar to that of the product prepared in Example 1.

[0069] Embodiment 6:

[0070] The difference from Example 1 is that the epoxy resin used is dicyclopentadiene epoxy resin.

[0071] The performance of the product prepared is similar to that of the product prepared in Example 1.

[0072] Embodiment 7:

[0073] The difference from Example 1 is that a combination of two or more of epoxy resins selected from the group consisting of novolac epoxy resin, biphenyl epoxy resin, naphthol epoxy resin and dicyclopentadiene epoxy resin is used.

[0074] The performance of the product prepared is similar to that of the product prepared in Example 1.

[0075] Comparative Example 1:

[0076] Prepare the raw materials: including 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silica powder (particle size 0.5um (53 parts) and 4um (27 parts)), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent, and 15 parts of butyl ester.

[0077] The degassed mixture was coated and baked by a coating machine to remove the solvent, first heated at 60°C, then heated at 95°C, and finally heated at 80°C, the baking time was controlled to be 17.5min, and the dry adhesive thickness was controlled to be 130um to obtain an epoxy film. The obtained epoxy film was hot-pressed at a temperature of 80°C and a pressure of 2Mpa.

[0078] Comparative Example 2:

[0079] Prepare the raw materials: including 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silica powder (particle size 0.5um (53 parts) and 4um (27 parts)), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent, and 15 parts of butyl ester.

[0080] The degassed mixture is coated and baked by a coating machine to remove the solvent. It is first heated at 60°C, then at 95°C, and finally at 80°C. The baking time is controlled to be 21 minutes, and the thickness of the dry glue is controlled to be 130um to obtain an epoxy film. The obtained epoxy film is hot-pressed at a temperature of 80°C and a pressure of 2MPa.

[0081] Comparative Example 3:

[0082] Prepare the raw materials: including 12 parts of phenolic epoxy resin, 6 parts of phenolic curing agent, 0.05 parts of imidazole accelerator, 80 parts of silica powder (particle size 0.5um (53 parts) and 4um (27 parts)), 0.3 parts of pigment, 1 part of coupling agent, 0.5 parts of toughening agent, 15 parts of butyl ester

[0083] The degassed mixture is coated and baked by a coating machine to remove the solvent. It is first heated at 60°C, then at 95°C, and finally at 80°C. The baking time is controlled to be 23 minutes, and the thickness of the dry glue is controlled to be 130um to obtain an epoxy film. The obtained epoxy film is hot-pressed at a temperature of 80°C and a pressure of 2MPa.

[0084] Film performance testing:

[0085] Equal amounts of films were taken from Examples 1 to 3 and Comparative Examples 1 to 3 for comprehensive performance testing.

[0086] The test results are shown in Table 1.

[0087]

[0088] Table 1

[0089] Experimental results analysis:

[0090] Example 1: The surface of the film is dry and has good surface condition; there is little solvent residue; the surface gloss of the film is matte; the film has good adhesion performance and no bubbles on the surface; the film is stored for 20 days at room temperature and has good stability; the gel time is 230s, the thermal conductivity of the film is 1.2w / mk, and the viscosity at high temperature is 600pa·s.

[0091] Example 2: The surface of the film is dry and has good surface condition; there is little solvent residue; the surface gloss of the film is matte; the film has good adhesion performance and no bubbles on the surface; the film is stored for 14 days at room temperature and has good stability; the gel time is 200s, the thermal conductivity of the film is 0.9w / mk, and the viscosity at high temperature is 350pa·s.

[0092] Example 3: The surface of the film is dry and has good surface condition; there is little solvent residue; the surface gloss of the film is matte; the film has good adhesion performance and no bubbles on the surface; the film is stored for 12 days at room temperature and has good stability; the gel time is 180s, the thermal conductivity of the film is 0.8w / mk, and the viscosity at high temperature is 280pa·s.

[0093] Comparative Example 1: The difference from Example 1 is that the silicon powder is matched differently, the baking temperature is higher, and the baking time is longer. Compared with the film material of Example 1, the film material of Comparative Example 1 has a high solvent content and cannot be well demolded, the room temperature storage stability is reduced, and the surface quality and thermal conductivity after natural film curing are reduced.

[0094] Comparative Example 2: The difference from Example 1 is that the silicon micropowder is matched differently, the baking temperature and time window are different, and the baking time is further extended on the basis of Comparative Example 1. The surface quality of the film material of Comparative Example 2 is not as good as that of Example 1, but the solvent residue can be reduced by baking at a higher temperature and for a longer time. The surface quality of the natural film after curing is better than that of Comparative Example 1, but at the same time, the room temperature storage stability is affected.

[0095] Comparative Example 3: The difference from Example 1 is that the silicon micropowder is matched differently, the baking temperature and time window are different, and the baking time is further extended on the basis of Comparative Example 2. The surface quality of the film material in Comparative Example 3 is not as good as that in Example 1, but through higher temperature and longer baking time, the solvent residue is further reduced, and the surface quality of the film material is better than that of Comparative Example 2. At the same time, the room temperature storage stability is sacrificed to a greater extent, and the shelf life is further reduced.

[0096] In summary, from the perspective of the macroscopic performance of the film material, the combination of raw materials such as epoxy resin, phenolic curing agent, imidazole accelerator, silica powder, pigment, coupling agent, toughening agent and fillers of different particle sizes achieves the purpose of improving friction stability, bonding performance and surface roughness. The introduction of fillers with particle sizes of 2um, 0.5um and 4um makes the solvent volatilize faster during the preparation process of the film, supplements the heat conduction channel, and improves the thermal conductivity of the film after curing. With the appropriate baking process window, it ensures that the various components are fully dissolved in each other, the fillers are evenly accumulated, and the influence of solvent residues on the surface dryness of the film is reduced.

[0097] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A thermally conductive epoxy film, characterized in that: Includes components by weight: Epoxy resin 10-12 parts, curing agent 5-12 parts, accelerator 0.015-0.11 parts, inorganic filler 28-80 parts, pigment 0.1-0.5 parts, coupling agent 0.4-1 parts, toughening agent 0.3-1.2 parts; The inorganic filler is silicon micropowder, and the silicon micropowder includes silicon micropowder with a particle size of 2 um, silicon micropowder with a particle size of 0.5 um, and silicon micropowder with a particle size of 4 um.

2. The thermally conductive epoxy film according to claim 1, characterized in that: The silicon micropowder with a particle size of 2 um accounts for 5 to 30% of the inorganic filler, the silicon micropowder with a particle size of 0.5 um accounts for 15 to 18.75% of the inorganic filler, and the silicon micropowder with a particle size of 4 um accounts for 60 to 75% of the inorganic filler.

3. The thermally conductive epoxy film according to claim 1, characterized in that: The epoxy resin includes phenolic epoxy resin, biphenyl epoxy resin, naphthol epoxy resin, dicyclopentadiene epoxy resin and a combination thereof.

4. The thermally conductive epoxy film according to claim 1, characterized in that: The curing agent includes a phenolic curing agent.

5. The thermally conductive epoxy film according to claim 1, characterized in that: The accelerator includes an imidazole accelerator.

6. The thermally conductive epoxy film according to claim 1, characterized in that: The toughening agent includes a core-shell toughening agent.

7. The thermally conductive epoxy film according to claim 1, characterized in that: The coupling agent includes a silane coupling agent.

8. The thermally conductive epoxy film according to claim 1, characterized in that: The pigment includes carbon black.

9. A method for preparing a thermally conductive epoxy film as claimed in any one of claims 1 to 8, comprising the following steps: Step S1, mixing: putting epoxy resin, curing agent, solvent and toughening agent into a stirrer and stirring to fully dissolve the resin and mix evenly to obtain a resin mixture; putting inorganic filler, pigment, coupling agent and toughening agent into a stirrer and stirring to obtain modified pigments and fillers; adding the modified pigments and fillers into the resin mixture, stirring, and then performing three-roll grinding and dispersion; then adding an accelerator, and performing vacuum degassing on the mixture to finally obtain a resin composition; Step S2, coating the resin composition on the base film; Step S3, surface drying, the base film is subjected to step-by-step heating to remove the solvent, and a three-stage heating method is adopted to obtain an epoxy resin film; Step S4, compounding the epoxy resin film and the protective film, and finally rolling them up.

10. The method for preparing a thermally conductive epoxy film according to claim 9, characterized in that: In step S1, the mixing speed of epoxy resin, curing agent, solvent and toughening agent is 300rpm-500rpm, and the stirring time is 30min; the mixing temperature of inorganic filler, pigment, coupling agent and toughening agent is 120°C, the stirring time is 1h, and the stirring speed is 800rpm-1000rpm; the stirring speed of modified pigment and resin mixture is 600rpm-800rpm, and the stirring time is 60min; the feed gap of three-roll grinding dispersion is 50um, the discharge gap is 30um, the feed gap is 30um, and the discharge gap is 10um; the vacuum degassing speed is 400rpm-600rpm, and the time is 6min-8min.

11. The method for preparing a thermally conductive epoxy film according to claim 9, characterized in that: In step S3, the first step temperature range is 40-60°C, the second step temperature range is 80-95°C, and the third step temperature range is 70-80°C.

12. The method for preparing a thermally conductive epoxy film according to claim 9, characterized in that: In step S4, the compounding temperature ranges from 80 to 110°C, and in step S2, the coating thickness is 1.0 to 1.2 times the thickness of the adhesive film after surface drying.

Citation Information

Patent Citations

  • Composite material for packaging and preparation method thereof

    CN102408681A

  • Single-component epoxy adhesive and preparation method thereof

    CN113736405A

  • Room-temperature curing epoxy heat-conducting adhesive for lithium battery, heat-conducting shell and preparation method of heat-conducting shell

    CN115322721A

  • Low-moisture-absorption type epoxy adhesive film and preparation method thereof

    CN115975526A

  • Mini LED screen packaging adhesive film, preparation method and packaging method

    CN116622320A